KLUB DRAMA BAHASA ARAB (NILAI PENDIDIKAN DAN PENGEMBANGAN LINGKUNGAN BAHASA ARAB BERBASIS DRAMA DI IAIN PONTIANAK) - Rahnang, Rahnang (Jurnal Al-Fatih, 2023)
This development research aims to develop the Arabic proficiency of IAIN Pontianak students through learning developed Arabic drama clubs. This type of research is R&D (research and development) which is used as a step to produce a product. The steps used, namely: needs analysis, product planning and data collection, initial product design, material expert validation, media expert validation, field trials, and final product refinement, so as to produce a prototype of drama-based Arabic learning products, The results showed that drama using Arabic can improve Arabic language skills in IAIN Pontianak students. The steps for implementing drama-based Arabic learning in Arabic drama clubs are discussion, tarjamah bi tasharruf and bi harfiyah (mufradatisim, fi'il, and letters), maharatul qira'ah (mukassyafah and shautiyah), maharatul istima' (sam'iyah and syafawiyah), maharatul kalam (nabr and tangim) expressed with gestures, face, and taste, maharatul kitabah is done with imla' madzur techniques, and taqdim is presenting learning results comprehensively.